(untitled) (Philippines, 2006)
This book includes many parts: preventing corruption in public administrations, the political sphere, and the business sector, sanctioning and prosecuting corruption and related offences, involving the public in the fight against corruption.
Keywords: Political corruption,Tham nhũng chính trị